Reassessing Brooks' law through consideration of manpower abilities - Farshchi, Mostafa; Yah Jusoh, Yusmadi; Azmi Murad, Masrah Azrifah (2011)
When software projects falls behind schedule, managers make any possible reactions to avoid any schedule slippage, mostly by adding new people to their projects. Adding more people to a late software project may cause negative impacts on the progress of the project as the result of assimilation time, training overhead and communication overhead. Consequently, a project manager faces difficulties to make the decision whether to add new members to his team or not. Therefore, in this research we attempted to address the problem by understanding how software project managers can minimize the negative impacts of adding new people to delayed software projects. This research aims to explore the effects of adding manpower to a late software project through personnel factors trade-off analysis. Particularly, this study has the intention to examine whether a significant schedule improvement can be achieved with proper consideration of the new manpower capabilities, skills and experience. For fulfillment of this research, we built a system dynamics model to simulate the dynamic behavior of the project progress when new members added with different ranges of personnel capabilities. In addition, an example case study has been run and related simulation results are compared with previous models. The result of this study shows that significant schedule improvement of a late project can be achieved if people with certain level of capabilities are added to a project.